Determination of $$\mathcal{C}\mathcal{P}$$ C P -violating HZZ interaction with polarised beams at the ILC - Cheng Li; Gudrid Moortgat-Pick (European Physical Journal C: Particles and Fields)
Abstract We study possible $${\mathcal{C}\mathcal{P}}$$ C P -violation effects of the 125 GeV Higgs to Z boson coupling at the 250 GeV ILC with transverse and longitudinal beam polarisation via the process $$e^+ e^- → HZ → H μ ^-μ ^+$$ e + e - → H Z → H μ - μ + . We explore the azimuthal angular distribution of the muon pair from the Z boson decay, and constructe $${\mathcal{C}\mathcal{P}}$$ C P -odd observables sensitive to $${\mathcal{C}\mathcal{P}}$$ C P -violation effects, where we derived this observable both by analytical calculations and by Whizard simulations. Particularly, we can construct two $${\mathcal{C}\mathcal{P}}$$ C P -odd observables with the help of transversely-polarised initial beams and improve the statistical significance of $${\mathcal{C}\mathcal{P}}$$ C P -violation effects by combining two measurements. We defined the asymmetries between the signal regions with different signs of the $${\mathcal{C}\mathcal{P}}$$ C P -odd observables, and determine the $${\mathcal{C}\mathcal{P}}$$ C P -violation effect by comparing with the SM 95% CL upper bound. In this paper, we setup a scenario which assumes that the total cross-section is always fixed while $${\mathcal{C}\mathcal{P}}$$ C P -violation is varying, and such a scenario helps us to determine the intrinsic $${\mathcal{C}\mathcal{P}}$$ C P -mixing angle limit around $$|ξ _{\mathcal{C}\mathcal{P}}|\sim 0.03~{\operatorname {rad}}$$ | ξ C P | ∼ 0.03 rad with (90%, 40%) polarised electron-positron beams and 5 $$\hbox {ab}^{-1}$$ ab - 1 integrated luminosity. In addition, we determine the $${\mathcal{C}\mathcal{P}}$$ C P -odd coupling limit $$|\widetilde{c}_{HZZ}|\sim 0.01$$ | c ~ HZZ | ∼ 0.01 as well, where we suppose that the SM tree-level cross-section is fixed and the $${\mathcal{C}\mathcal{P}}$$ C P -violation is the varying additional contribution. Comparing with the analysis with unpolarised beams, the sensitivity to the $${\mathcal{C}\mathcal{P}}$$ C P -violation effect can be improved by transverse or longitudinal polarisation.